The evolution of financial architecture supporting the BRICS: Reshaping the global financial order? - Viana de Castro, S. K.; Santiago, A. R. (Frontiers in Political Science, 2025)
Introduction: The financial architecture underpinning the BRICS has undergone significant evolution, reflecting broader changes in global economic governance. As a coalition of major emerging economies, the BRICS have sought to develop alternative financial mechanisms that enhance economic cooperation, reduce dependence on Western-dominated institutions, and promote a multipolar global financial order. This study explores the structural dynamics of these financial arrangements, analyzing their evolution, operational structures, and implications for global financial governance. A key component of this architecture is the New Development Bank (NDB), created to finance infrastructure and sustainable development projects within the BRICS countries and beyond. The NDB, together with other mechanisms such as the Contingent Reserve Arrangement (CRA), represents a strategic effort to provide alternative sources of financing while mitigating external financial vulnerabilities. Methods: This research, based on the analysis of official policy documents, aims to answer the following research questions: To what extent does the financial architecture developed by the BRICS, particularly through the New Development Bank and the Contingent Reserve Arrangement, represent a counterinstitutionalization strategy in relation to global financial governance? Can the patterns of action and cooperation promoted by the BRICS through their financial mechanisms be interpreted as evidence of the Chinese revisionist vision embodied by the BRICS? Results and discussion: Our first hypothesis is that it is possible to state that the BRICS constitute a challenge to international financial governance based on the counter-institutionalization strategy. In this way, the BRICS do not seek to replace the established global governance system, but rather to change it, generating adaptations. The second hypothesis, in turn, is that the BRICS appear to have incorporated the Chinese vision of global governance, by configuring themselves as a revisionist group and not a “full reformist” group, which means that the strategies of contesting the status quo seek to complement existing institutions and norms and not to replace them. By examining the evolution and structural dynamics of these financial arrangements, this study contributes to a broader understanding of the role of emerging economies in reshaping the global financial order.